Mobile-based Smart Farmer Application as a Forum and Learning Center for Horticultural Crop Cultivation: Aplikasi Mobile Petani Pintar sebagai Wadah Forum dan Pembelajaran Budidaya Tanaman Hortikultura - Findawati, Yulian; Sutarman; Rosid, Muhammad Alfan; Ramadhan, Aldo Reghan; Setiawan, Ari (Procedia of Social Sciences and Humanities, 2022)
The driving wheel of the state's economy Alignment to small farmers must also be demonstrated by optimizing the role of extension workers. Agricultural extension workers can take advantage of digital information technology so that assistance can be done anytime and anywhere. Therefore, an application for an Android-based online forum and learning forum is needed to make it easier for farmers to get learning information about PEST management, nurseries and planting. With technology that supports learning, counseling, online forums, it is hoped that it will facilitate communication during the Covid-19 pandemic. is an online learning media application for farmers. Where farmers can see learning videos, bibliography, agricultural material, extension videos, discussions with farming communities and questions and answers with agricultural experts from both the government and universities. Due to the Covid pandemic, counseling communication was somewhat hampered. This application is built using the PHP, Java and MySQL programming languages. With this application, it is hoped that it will facilitate the process of learning, counseling and consulting by farmers